2016
DOI: 10.5296/jse.v6i1.8799
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effect of One-way versus Two-way Tasks on Iranian Intermediate EFL Learners’ Phrasal Verb Learning

Abstract: The aim of this study was to investigate the effect of one-way and two-way tasks, as two various techniques for teaching vocabulary, on Iranian intermediate EFL learners' phrasal verb learning. The participants in this study were sixty EFL learners majoring in TEFL, all of whom were in the second semester of academic year 2015. In order to establish a homogenized group, a test of proficiency titled CELT was administered to ninety sophomore students, and sixty were selected to serve the purpose of the study. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…They are, also, consistent with the results obtained by Nosratinia, Amini and Sarabchian (2013) proving the effectiveness of making informed guesses about contextualized PVs meanings in fostering English majors' PVs acquisition. Besides, the present study results conform with the findings reached by Khodareza (2016) supporting the positive impact of collaborative tasks on PVs learning. Additionally, the current study findings are consistent with the results of Kim's (2019) study proving that combining images and video clips with written texts enhanced EFL college students' PVs learning.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…They are, also, consistent with the results obtained by Nosratinia, Amini and Sarabchian (2013) proving the effectiveness of making informed guesses about contextualized PVs meanings in fostering English majors' PVs acquisition. Besides, the present study results conform with the findings reached by Khodareza (2016) supporting the positive impact of collaborative tasks on PVs learning. Additionally, the current study findings are consistent with the results of Kim's (2019) study proving that combining images and video clips with written texts enhanced EFL college students' PVs learning.…”
Section: Discussionsupporting
confidence: 91%
“…Based on their study findings, it was concluded that modifying input through either simplification or elaboration facilitated PVs acquisition and recall among the study participants. Additionally, Khodareza (2016) found that collaborative tasks fostered Iranian intermediate level TEFL majors' PVs learning. Furthermore, Vazirabad and Farrokhi (2021) proved that playing digital games in formal instructional settings enhanced PVs learning and comprehension among Iranian EFL intermediate level learners.…”
Section: Techniques Used To Foster Pvs Acquisitionmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on the present quasiexperimental study, there is a difference in the effect of one-way and two-way tasks on Iranian pre-intermediate EFL learners' lexical knowledge and long-term retention of lexis. These findings support the previous claims for the efficacy of one-way and two-way tasks on learners' lexical learning (Khodareza & Shabani, 2016 Furthermore, the findings lend support to a previous study which has demonstrated the benefits of task-based approach on vocabulary learning and enhancement in ESP courses (Hedayatipanah, Mirzaei & Azizifar, 2015). Based on their results, they concluded that task-based approach was more effective in teaching technical vocabularies.…”
Section: Discussionsupporting
confidence: 80%